PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN FLASHCARD TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Lutvia Nurul Afwah; Zuida Ratih Hendrastuti; Yesi Franita (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The purpose of this study is to analyze the effect of the flashcard-assisted Problem Based Learning learning model on the mathematical problem solving ability. The research design used in this study is quasi experimental design. The research method used is quantitative research. The population in this study was the entire class VIII which amounted to 120 students, then for the sample two classes were taken, namely class VIII A as an experimental class and class VIII B as a control class. The sample in this study was taken by cluster random sampling technique. Data collection techniques include interviews, observations, tests, validation, and documentation. The data analysis technique used is the analysis of the average difference in significance test between the two groups with test prerequisites, namely normality tested using the Liliefors test and homogeneity tested using the Bartlett test. Based on the results of analysis and data processing using the t-test, it was obtained that the Sig. (2-tailed) value < 0.05 which means that the  rejected and  with a significant level of 5%. Based on these results, it can be concluded that there is an influence of the flashcard-assisted Problem Based Learning learning model on the mathematical problem solving ability of grade VIII. This can be a reference that the flashcard-assisted Problem Based Learning model can be used as a relevant learning model to improve students' mathematical problem-solving skills